Sleep disturbances and physical health problems in caregivers of children with ASD. (June 2021) - Lovell, Brian; Elder, Greg J.; Wetherell, Mark A.
Abstract: Objectives: Caregivers of children with autism spectrum disorder self-report more physical health problems than controls. Sleep disturbances are also more prevalent in caregivers, and are positively associated with physical health problems. The negative impact of caring for a child with ASD on physical health therefore, might occur indirectly via poorer sleep. Methods: Participants, of which n = 43 were caregivers and n = 17 were controls, completed self-report measures of physical health problems and, to capture objective measures of sleep, wore an actigraphy device. Results: Physical health problems were greater in caregivers, as were subjective reports of disturbed sleep. Objectively, waking after sleep onset (WASO) and average number of awakenings were higher, as was sleep latency, and sleep efficiency was poorer, in caregivers. Total sleep time however, was greater in caregivers, as was time in bed. Physical health problems, while unrelated to actigraphy measures, were positively associated with self-reported sleep disturbances. Caregivers' increased risk for physical health problems occurred indirectly via greater self-reports of disturbed sleep. Conclusions: Interventions that help alleviate caregivers' sleep disturbances might be effective, by reducing physical health problems, for improving quality of provided care, and this might be explored in future research.